102 Association of Medicaid Expansion Under the Affordable Care Act with Access to Elective Spine Surgical Care. (1st April 2022) - Greenberg, Jacob K.; Brown, Derek; Olsen, Margaret; Ray, Zack
Abstract : INTRODUCTION: The Affordable Care Act expanded Medicaid eligibility in many states, improving access to some forms of elective healthcare in the United States. Whether this effort increased access to elective spine surgical care is unknown. METHODS: We evaluated elective spine surgeries using state inpatient databases from 2011-2016 from 10 states that did and four states that did not expand Medicaid access in 2014. Patients aged 18-64 years undergoing elective spine surgery were included. We used a quasi-experimental difference-in-difference design to evaluate the impact of Medicaid expansion on hospital procedure volume and payer mix, independent of any time-dependent trends. Subgroup analyses were conducted that stratified results by cervical fusion, thoracolumbar fusion, and non-instrumented surgery. RESULTS: We identified 218, 648 surgeries in 10 Medicaid expansion states and 118, 693 in 4 non-expansion states. Expansion states showed an increase in overall and Medicaid but not privately insured volumes in 2014, compared to decreased or steady volumes in non-expansion states.These changes led to a 17% (95% CI 2%-35%) increase in mean hospital spine surgical volume, and a 23% (95% CI -0.3%-52%) increase in Medicaid volume associated with Medicaid expansion. Privately insured surgical volumes did not change significantly. The rise in Medicaid volumes led to a shift in payer mix, with the proportion of Medicaid patients rising by 6.1 percentage points (95% CI 4.0-8.1), and the proportion of private payers decreasing by 6.9 percentage points (95% CI 4.7-9.1). While the magnitude of the effects varied, these trends were similar across procedure subgroups. CONCLUSION: Medicaid expansion under the Affordable Care Act was associated with an economically and statistically significant increase in spine surgery volume and the proportion of patients with Medicaid insurance.